Severe Methanol Poisoning with Supralethal Serum Formate Concentration: A Case Report - Nurieva, Olga; Kotikova, Katerina (Medical principles and practice, 2015)
OBJECTIVE: To present a case of survival without visual and central nervous system sequelae at a formate concentration of twice the reported lethal level. CLINICAL PRESENTATION AND INTERVENTION: This was a case of a 33-year-old man who ingested 1 liter of a toxic mixture of methanol and ethanol. Upon admission, he presented with anxiety, tachycardia and hypertension and had a serum formate level of 1,400 mg/l (normal range 0.9-2.1 mg/l), a methanol level of 806 mg/l (normal range 2-30 mg/l), an undetectable ethanol concentration and a normal lactate level. A 10% solution of ethanol and folinic acid was administered intravenously and two 8-hour sessions of intermittent hemodialysis were performed. The patient was discharged on the fifth day without sequelae of poisoning. The follow-up examinations 3 months and 2 years later revealed no damage to the basal ganglia. The patient had normal visual-evoked potential and findings on optical coherence tomography. The genetic analysis revealed a rare minor allele for the gene coding CYP2E1 enzyme of the microsomal ethanol oxidizing system. CONCLUSION: The patient survived acute methanol poisoning without long-term sequelae despite a high serum level of formic acid upon admission.
Keywords: formiáty; Renal Dialysis; methanol; dospělí; otrava; Adult; Formates; ethanol; Ethanol; Humans; dialýza ledvin; mužské pohlaví; Male; lidé; leukovorin; Poisoning; Leucovorin; Methanol